Annona muricata aqueous extract suppresses T47D breast cancer cell proliferation - Ika Fidianingsih (Universa Medicina, 2014)
Background Cancer is a dreadful disease caused by abnormal and uncontrolled cell division. Annona muricata L, also known as soursop, is useful as an anticancer herbal medication since its leaves, seeds and fruits contain active compounds called annonaceous acetogenins. The objective of this study was to scientifically justify the traditional application of soursop for anticancer treatment in the community, by comparing the antiproliferative effect of Annona muricata L leaf, seed and fruit aqueous extracts on T47D breast cancer cells.